Investigating Factors Contributing to Poor Performance in Teaching and Learning of N3 Assembly Drawing: A Case of uMgungundlovu TVET College - Mlambo, Philani Brian; Mkhwanazi, Mthokozisi Sakhile (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
Poor performance in Assembly Drawing (AD) has been a significant issue in Engineering Graphics and Design (EGD) in high schools and TVET colleges. This poor performance in AD, which is a crucial component of the EGD exam, leads to students not performing well in Grade 12 and consequently limits their entry into engineering programs in TVET colleges. Consequently, this study aims to investigate the contributing factors to poor performance in the teaching and learning of AD among N3 students. To achieve the objectives of this study, a mixed research approach was employed, and data was collected through semi-structured interviews and the Purdue Spatial Visualization Test (PSVT). A purposive sampling method was used to select four Engineering Drawing (ED) lecturers and 45 N3 Engineering Drawing students to participate in this study. Furthermore, Piaget's perception and imagery theory and Pedagogical Content Knowledge (PCK) were utilized as frameworks underpinning this study. The interview results were analyzed using thematic analysis, while the data from the PSVT was analyzed using the Statistical Package for Social Sciences (SPSS). The findings of this study indicate that N3 students have very low spatial visualization skills, and the negative attitude displayed by both students and lecturers towards the teaching and learning of AD contributes to poor performance in N3 ED. The findings further revealed that the lack of drawing-related teaching qualifications among lecturers also contributes to poor performance in AD. Furthermore, the quantitative findings show that the students achieved a mean score of 16.82, with a standard deviation of 8.389, indicating poor performance on the PSVT test. One limitation of this study is the small number of lecturers interviewed (four), which makes it difficult to generalize the results. Therefore, future studies should include a larger sample size of lecturers. This study recommends that lecturers be hired based on their relevant teaching qualifications and further suggests the use of technology to enhance students' spatial visualization skills and improve their performance in AD.